PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PENELITIAN VARIASI GENETIK KERBAU (BUBALUS BUBALIS) TORAJA UTARA UNTUK MATAKULIAH TEKNIK ANALISIS BIOLOGI MOLEKULER DI UNIVERSITAS NEGERI MALANG - Fadli Mermang; Abdul Gofur; Mohamad Amin (Universitas Sebelas Maret, 2014)
Swamp buffalo is the most high-value animal in North Toraja Regency culture, in addition to being a work animal and transaction tools are also used as offerings in the ceremony signs solo' and signs tuka' North Toraja society. The purpose of this study was to describe the variation of the District Rantepao buffalo genotypes and North Toraja Regency Tikala using microsatellite developed as a multimedia course Analysis Techniques for Molecular Biology at the State University of Malang.Stages in this study include descriptive exploratory research phase and the development phase of multimedia for learning media. Observations of genetic variation patterns do start stage followed by DNA isolation using agarose gel electrophoresis was performed after PCR using HEL 09 and INRA 032 was followed by gel electrophoresis polyacrilamid. Electrophoresis obtained from the gel bands were then analyzed using the results of research genepop.Analysis of interactive multimedia development using media expert validation of a questionnaire shows the effectiveness of 91.67%, 87.50% the attractiveness, interactivity efficiency 100% and 91.67% with qualifying very well. For validation of learning materials experts show presentation purposes 95%, 89.29% material, the effectiveness of 83.33 and 93.75% interactivity with excellent qualifications. Analysis of a small group test with a sample of 12 people was 80.60% with good qualifications. Interactive media that had been developed can be used by lecturers and students biology education courses to better understand the basic principles and appropriate procedures in the course of TABM. Keywords: buffalo, interactive multimedia, genetic variation